The impact of environmental regulation on clean innovation: Are there crowding out effects? - Nicola Benatti; Martin Groiss; Petra Kelly; Paloma López-García (European Central Bank (ECB), 2024)
We examine the extent to which environmental regulation affects innovation and which policy types provide the strongest incentives to innovate. Using a local projection framework, we estimate the regulatory impact on patenting activity over a five-year horizon. As a proxy for environmental policy exposure, we estimate firm-level greenhouse gas emissions using a machine learning algorithm. At the country-level, policy tightening is largely associated with no statistically significant change in environmental technology innovation. At the firm-level, however, environmental policy tightening leads to higher innovation activity in technologies mitigating climate change, while the effect on innovation in other technologies is muted. This suggests that environmental regulation does not lead to a crowding-out of non-clean innovations. The policy type matters, as increasing the stringency of technology support policies and non-market based policies leads to increases in clean technology patenting, while we do not find a statistically significant impact of market-based policies.
Keywords: O44; Q52; Q58; 330; Environmental regulation; Innovation; Emissions; Porter hypothesis; Euro Area